Analisis Pengaruh Komunikasi Internal dan Organizational Citizenship Behavior terhadap Retensi Karyawan - Syaifudin, Arif; Edward, Yusuf Ronny; Pujiastuti, Endah; Sekamdo, Muhammad Aga; Haes, Putri Ekaresty (Jurnal EMT KITA, 2026)
This study aims to analyze the influence of internal communication, OCB on employee retention at PT SJB Kudus. The background of this study is driven by the high rate of employee turnover, which can disrupt operational sustainability and organizational performance stability. A quantitative approach was used using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the relationship between variables. Respondents consisted of 100 permanent employees selected through a census. Data were collected using a five-point Likert scale questionnaire that has been tested for validity and reliability. Data analysis was conducted using SmartPLS 4. The results of the study indicate that internal communication significantly affects employee retention. Furthermore, OCB has a significant positive influence on employee retention. These findings highlight the importance of effective internal communication practices, and strategies to enhance OCB in encouraging out-of-role behavior and reducing employee retention.